Compromiso, recursos, emprendimiento exportador y resultados empresariales - Antonio Navarro-García; Manuel Rey-Moreno; Ramón Barrera-Barrera (RAE: Revista de Administração de Empresas, 2017)
The current research has two aims. Firstly, starting from the premises of the Resource-Based View (RBV) to know how specific internal factors (resources and export commitment) can influence an exporting firm’s level of entrepreneurship in foreign markets. Secondly, to find out what the effect of export entrepreneurship is on business results. The relationships proposed are clearly reflected in a conceptual model which will be verified from a multisectorial sample of 212 Spanish exporting firms. The results reveal that: a) export entrepreneurship positively depends on export commitment and the resources associated with experience and structure; b) there is a positive effect of the level of export entrepreneurship on business results. It is recommended that export firms develop accelerated internationalization processes, be present in numerous countries simultaneously and have a high export intensity.